2011
DOI: 10.1021/es201619r
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Depth of Localized Radioactive Contamination by 137Cs and 60Co in Sand with Principal Component Analysis

Abstract: A method to determine the depth of buried localized radioactive contamination nonintrusively and nondestructively using principal component analysis is described. The γ-ray spectra from two radionuclides, cesium-137 and cobalt-60, have been analyzed to derive the two principal components that change most significantly as a result of varying the depth of the sources in a bespoke sand-filled phantom. The relationship between depth (d) and the angle (θ) between the first two principal component coefficients has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…To exploit the additional information that exists as a result of this, principal component analysis (PCA) has been used to highlight the two lowest-order components of this dependence. When these are plotted as a function of depth, a dependence is observed that can be used as a calibration curve in a similar way to the approach depicted in Figure 4 (Adams et al, 2011). This is shown in Figure 5 for the case of 137 Cs.…”
Section: Commissioning Quantitative Measurementsmentioning
confidence: 83%
See 3 more Smart Citations
“…To exploit the additional information that exists as a result of this, principal component analysis (PCA) has been used to highlight the two lowest-order components of this dependence. When these are plotted as a function of depth, a dependence is observed that can be used as a calibration curve in a similar way to the approach depicted in Figure 4 (Adams et al, 2011). This is shown in Figure 5 for the case of 137 Cs.…”
Section: Commissioning Quantitative Measurementsmentioning
confidence: 83%
“…Two spectra for a sealed, point caesium-137 source inserted at depths 5 mm (circles) and 50 mm (triangles) in a silica-sand filled phantom. The X-ray photopeak at 5 mm (circles trace, left) is absent at 50 mm, while the 662-keV photon (both traces, right) is present at both depths, but significantly attenuated at 50 mm compared with 5 mm by approximately 50% (Adams et al, 2011) Figure 3. A photograph of the sand-filled phantom designed and commissioned to support this research, with most of the sand removed to expose the calibrated slider (Adams et al, 2011;Shippen and Joyce, 2011) Figure 4.…”
Section: Commissioning Quantitative Measurementsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, traditional methods of depth estimation such as core sampling and logging are slow and have limited spatial sampling extent because of their intrusive nature. Furthermore, the nonintrusive methods reported in [5,[7][8][9][10][11][12][13][14] are either based on regressional models whose parameters typically have no physical significance or are limited to specific radioactive sources. Also, other nonintrusive methods reported in [15,16] use specialised shielding and collimator arrangements while those that employ machine learning [17][18][19] require significant amount of data to train the algorithms.…”
Section: Introductionmentioning
confidence: 99%